A Case of Malignant Melanoma Arising in Mediastinal Malignant Teratoma. (31st December 2018) - Nozaki, Ikuma; Tone, Yumi; Yamanaka, Junko; Uryu, Hideko; Shimizu-Motohashi, Yuko; Sato, Noriko; Matsushita, Takeji
Abstract : We report about a 14-year-old boy who presented with an anterior mediastinal mass that was diagnosed as malignant teratoma. Surgical resection was performed along with pre- and postoperative chemotherapy. Although elevated alpha-fetoprotein became negative, he experienced pain in his right hip joint 3 months after resection. Systematic evaluation revealed multiple locations of metastasis, and the pathological diagnosis based on bone biopsy was malignant melanoma originating from malignant teratoma, which rapidly progressed. He died 15 months after diagnosis of the original malignant teratoma. Diagnosing and treating malignant transformation of teratoma, including malignant melanoma, is difficult because it is very rare. To our knowledge, this is the second reported case of malignant melanoma arising from a mediastinum malignant teratoma, with both cases having a poor prognosis. In addition to the follow-up of tumor markers, systematic evaluation, including imaging, should be considered even after remission to monitor malignant transformation of teratoma. We expect to establish a successful therapy and improve mortality rate after more such cases are accumulated.